Applying decision-making capacity criteria in practice: A content analysis of court judgments. - Nuala B Kane; Alex Ruck Keene; Gareth S Owen; Scott Y H Kim (PLoS ONE)
Background/objectives Many jurisdictions use a functional model of capacity with similar legal criteria, but there is a lack of agreed understanding as to how to apply these criteria in practice. We aimed to develop a typology of capacity rationales to describe court practice in making capacity determinations and to guide professionals approaching capacity assessments. Methods We analysed all published cases from courts in England and Wales [Court of Protection (CoP) judgments, or Court of Appeal cases from the CoP] containing rationales for incapacity or intact capacity(n = 131). Qualitative content analysis was used to develop a typology of capacity rationales or abilities. Relationships between the typology and legal criteria for capacity [Mental Capacity Act (MCA)] and diagnoses were analysed. Results The typology had nine categories (reliability: kappa = 0.63): 1) to grasp information or concepts, 2) to imagine/ abstract, 3) to remember, 4) to appreciate, 5) to value/ care, 6) to think through the decision non-impulsively, 7) to reason, 8) to give coherent reasons, and 9) to express a stable preference. Rationales most frequently linked to MCA criterion 'understand' were ability to grasp information or concepts (43%) or to appreciate (42%), and to MCA criterion 'use or weigh' were abilities to appreciate (45%) or to reason (32%). Appreciation was the most frequently cited rationale across all diagnoses. Judges often used rationales without linking them specifically to any MCA criteria (42%). Conclusions A new typology of rationales could bridge the gap between legal criteria for decision-making capacity and phenomena encountered in practice, increase reliability and transparency of assessments, and provide targets for decision-making support.